2023
DOI: 10.3389/fneur.2023.1164756
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and neurological disease: a narrative review

Abstract: Hyperuricemia often accompanies hypertension, diabetes, dyslipidemia, metabolic syndrome, and chronic renal disease; it is also closely related to cardiovascular disease. Moreover, several epidemiological studies have linked hyperuricemia and ischemic stroke. However, uric acid may also have neuroprotective effects because of its antioxidant properties. An association between low uric acid levels and neurodegenerative diseases has been suggested, which may be attributed to diminished neuroprotective effects as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 85 publications
(124 reference statements)
0
0
0
Order By: Relevance
“…Whereas, another study discussing the relationship between uric acid and osteoporosis suggested that hyperuricemia could have a protective effect against neurodegenerative diseases and may reduce the risk of bone fractures by affecting bone mineral density ( 24 ). In the narrative review by Otani et al ( 36 ), the authors investigate the complex role of uric acid in neurological disorders. It details how uric acid’s antioxidant properties might confer neuroprotection by scavenging free radicals and inhibiting lipid peroxidation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas, another study discussing the relationship between uric acid and osteoporosis suggested that hyperuricemia could have a protective effect against neurodegenerative diseases and may reduce the risk of bone fractures by affecting bone mineral density ( 24 ). In the narrative review by Otani et al ( 36 ), the authors investigate the complex role of uric acid in neurological disorders. It details how uric acid’s antioxidant properties might confer neuroprotection by scavenging free radicals and inhibiting lipid peroxidation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the narrative review by Otani et al ( 36 ), the authors investigate the complex role of uric acid in neurological disorders. It details how uric acid’s antioxidant properties might confer neuroprotection by scavenging free radicals and inhibiting lipid peroxidation ( 36 ). Notably, the review presents evidence indicating that higher uric acid levels might be linked to a decreased risk and slower progression of Parkinson’s disease ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of uric acid in neurological diseases are likely to vary greatly between stroke, a vascular disease, and Parkinson's and Alzheimer's diseases, which are neurodegenerative diseases [156]. A systematic review of umbrella reviews revealed a significant association of high serum uric acid levels with a decreased risk of several neurological diseases (i.e., Parkinson's disease, Alzheimer's disease, dementia, multiple sclerosis, neuromyelitis optica, and amyotrophic lateral sclerosis) [157].…”
Section: Neurological Diseasesmentioning
confidence: 99%